Leuconostoc mesenteroides M13: optimization of bioprocesses and antioxidant property for food industry application - COLARES, Heloísa Carneiro; TARABAL, Vinícius Souza; MEIRA, Hiure Gomes Ramos; SILVA, Daniela Regiane da; ABUD, Yuri Komatsu Damas; SANT’ANNA FILHO, Celso Barbosa de; PARREIRA, Adriano Guimarães; CORTES , Vanessa Faria; SILVA, Jose Antonio da; GRANJEIRO, José Mauro; MAGALHÃES, Juliana Teixeira de; GONÇALVES , Daniel Bonoto; et al. (Food Science and Technology, 2025)
Several reactive oxygen species are related to physiological functions but also play roles in the development of certain human diseases. Reactive oxygen species are counterbalanced by a physiological defense network such as antioxidants. Probiotic strains have been used as natural antioxidants, but its viable scalability is a challenger. The objective of this work was to optimize the bioprocesses of Leuconostoc mesenteroides M13 and evaluate its antioxidant activity and its shelf-life. The optimized production of M13 biomass was 2,542% greater than non-optimized processes, resulting in a yield of 2.67 × 1010 CFU mL-1 under conditions comprising 13.67 g L-1 of yeast extract and .73 g L-1 of magnesium sulfate. The aggregated spherical structure observed in scanning electron microscopy may have a certain protective effect. The viability of the lyophilized strain storage at 4°C was maintained for a period of up to 8 months. Antioxidant activity assays revealed efficacies for intact and lysed cells as 81 and 65%, respectively. The survival rate of the M13 strain in the presence of hydrogen peroxide was observed at 86% (1.0 mM for 8 h). M13 demonstrated a cost-effective strategy for probiotic application in the food industry as an antioxidant supplement.